Shiras family papers
Letter (1873 February 18) from Alexander Shiras to Samuel Shiras discussing the Philadelphia and Pittsburgh, Pa., branches of the Shiras family; letter (1885 June 8) from J.O. Shiras to Oliver P. Shiras relating family news; family Bible pages listing birth and death dates of various family members; and leaflet giving information on the Shiras family plot in the burial ground of Trinity Cathedral, Pittsburgh.
Positive photocopies and handwritten transcript.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Shiras, Alexander, -- 1813-1894 -- Correspondence; Shiras, J. O. -- Correspondence; Shiras, Oliver P. -- 1830- -- Correspondence; Shiras, Samuel -- Correspondence; Shiras family; Trinity Cathedral (Pittsburgh, Pa.); Burial -- Pennsylvania -- Pittsburgh; Pennsylvania -- Social life and customs; Philadelphia (Pa.) -- Social life and customs; Pittsburgh (Pa.) -- Social life and customs